Acute and chronic response of supervised band-elastic resistance exercise in systemic cytokines levels of bipolar disorders and schizophrenia individuals: A pilot study - Dos Santos, Gustavo Gusmão; Bachi, André Luis Lacerda; Rangel, Sara Coelho; da Silva Nali, Luiz Henrique; Daca, Timóteo Salvador Lucas; do Amaral, Jonatas Bussador; Juliano, Yara; Natrielli-Filho, Decio Gilberto; Rossi, Fabricio Eduardo [UNESP]; Gil, Saulo; Lafer, Beny; Neves, Lucas Melo (Elsevier, 2025)
Despite earlier research demonstrating the immunomodulatory effects of acute and chronic exercise in many medical illnesses, there is a lack of literature evaluating the acute and chronic effects of exercise on the cytokine levels in individuals with bipolar disorder (BD) or schizophrenia (SCH). This study aims to examine the acute effects of resistance exercise on cytokines and the chronic effects of resistance exercise by 10 weeks on cytokine levels, symptoms of disease, and muscular strength in individuals with BD and SCH. The included individuals (N=10) performed a single session of band-elastic resistance exercises (six exercises, 3 sets of 12–15 repetitions, 60 seconds of interval between sets). A sub-sample (N=6) of individuals performed a supervised band-elastic resistance exercise program (2 times a week, for 10 weeks, 6 exercises, 3 sets of 12–15 repetitions, 60 seconds of interval). We verified for acute effects: IL-2 (P=0.0085) and IL-4 (P=0.0253) levels increased, while IL-6 decreased (P=0.0435), and for chronic effects: increased IL-2 and IL-4 levels (significant effect size - Pre vs Post), a decrease in disease symptoms, and an increase in muscular strength. This study adds to what is already known about how resistance exercises affect people with BD and SCH in both short-term (systemic cytokines levels) and long-term (symptoms of disease, muscular strength, and systemic cytokines levels).
Keywords: Inflammation; Mental health; Physical activity